A comprehensive examination of the psychometric properties of the Appearance Anxiety Inventory and its adaptation into Turkish - Taşdelen Karçkay, Arzu; Aslan, Emre; Bakalım, Orkide (Anales de Psicología / Annals of Psychology, 2026)
Appearance anxiety, characterized by an individual’s negative perception of their body image and stress caused by the possibility of their appearance being evaluated by others, can have negative effects on the lives of emerging adults. The aim of this study is to adapt the Appearance Anxiety Inventory (AAI) to Turkish, and also to examine the psychometric properties of the scale comprehensively using classical test theory and some modern measurement approaches. For this purpose, the psychomet ric properties of the AAI in Turkish culture were examined in a sample of emerging adults (N = 520). Confirmatory factor analysis supported the single factor structure of the AAI. Item response theory analysis revealed that the scale items had sufficient discrimination parameters for levels of appearance anxiety. Network analysis determined that the item with the highest centrality was that regarding the individual hiding or changing his or her appearance. The findings of the study indicate that the AAI has sound psychometric properties that can be used in the assessment of ap pearance anxiety in emerging adults in the Turkish population.